Theoretical Study Of The Application Of The Part And Whole Method In Physical Education In Memorizing The Movements Of Senam Anak Indonesia Hebat (Saih) - Afrilliyan, Arrendi; Andes Permadi; Fadhlil Hadi; Nurul fajar muslimah ningrum; Rizky, Oddie Barnanda; Ari Sutisyana; Defliyanto (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2025)
The main objective of this study is to determine the extent to which the part and whole approach helps Physical Education students at Bengkulu University in memorizing the series of movements of Senam Anak Indonesia Hebat (SAIH). Students often experience difficulties in memorizing and practicing rhythmic gymnastics movements due to the complexity and accuracy required in the routine. This research utilized a qualitative approach by conducting a comprehensive assessment of various academic publications and previous studies. Students demonstrated better understanding and retention of the routines when taught using the Part and Whole approach. This technique involves breaking down movements into component parts and then recombining them into a whole. This strategy has been shown to improve motor skills, movement accuracy, and speed of adaptation, according to previous research conducted by experts. As a result, the part and whole approach is considered a highly effective method for teaching rhythmic gymnastics as it provides a sustainable framework for improving memorization skills in physical education.